Teacher's Dilemma: Facing Endless Curriculum Changes - Loso Judijanto; Hudson Sidabutar; Imelda Christine Kansil (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2024)
This article discusses the dilemma faced by teachers in the face of endless curriculum changes. Constant changes in education standards require teachers to be adaptive and innovative, although they often lack adequate training and support. This difficulty highlights the importance of approaches involving professional capacity building, collaboration between teachers and psychosocial support to help teachers navigate these challenges. With the right strategies, it is hoped that teachers will be more competent and motivated to implement the new curriculum, resulting in significantly improved learning quality and student achievement.